2000
DOI: 10.1021/ma991970d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydroperoxides in Solid Polyethylene by MAS 13C NMR and EPR

Abstract: Abstract'3C-enriched polyethylene was subjected to y-irradiation in the presence of air at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…This resonance is identified with hydroperoxides and/or dialkyl peroxides (peak a in Figure 1). In their solid-state 13 C NMR analysis of γ-irradiated, 13 C enriched polyethylene films, Assink et al 10 found a similar resonance at ∼85 ppm which they attributed to secondary hydroperoxides. (c) methyl ketones; (d) esters and/or peresters; (e) carboxylic acids and/or esters; (f) in-chain ketones; (g) ketals and/or acetals.…”
Section: Resultsmentioning
confidence: 99%
“…This resonance is identified with hydroperoxides and/or dialkyl peroxides (peak a in Figure 1). In their solid-state 13 C NMR analysis of γ-irradiated, 13 C enriched polyethylene films, Assink et al 10 found a similar resonance at ∼85 ppm which they attributed to secondary hydroperoxides. (c) methyl ketones; (d) esters and/or peresters; (e) carboxylic acids and/or esters; (f) in-chain ketones; (g) ketals and/or acetals.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed the vitamin E-stabilized UHMWPE development with the following questions in mind: (1) What is the rationale behind protecting irradiated UHMWPE against oxidation by vitamin E? (2) What are the effects of vitamin E on the microstructure, tribologic, and mechanical properties of irradiated UHMWPE? (3) Is vitamin E expected to affect the periprosthetic tissue negatively?…”
Section: Discussionmentioning
confidence: 99%
“…(2) What are the effects of vitamin E on the microstructure, tribologic, and mechanical properties of irradiated UHMWPE? (3) Is vitamin E expected to affect the periprosthetic tissue negatively?…”
Section: Introductionmentioning
confidence: 99%
“…These peroxy radicals, in the absence of an antioxidant such as vitamin E, abstract a hydrogen atom from other polyethylene chains, creating new primary free radicals, which can then react with oxygen to further this chain of reactions [1,60]. When peroxy free radicals react with hydrogen, they form hydroperoxides, which are not stable and degrade into oxidation products, mainly ketones, esters, and acids [2,3,16,17]. The formation of these oxidation products is accompanied by chain scission and a decrease in the molecular weight of polyethylene, reducing its mechanical properties [14,37].…”
Section: Introductionmentioning
confidence: 99%